H-NS Mutation-Mediated CRISPR-Cas Activation Inhibits Phage Release and Toxin Production of Escherichia coli Stx2 Phage Lysogen - Fu, Qiang; Li, Shiyu; Wang, Zhaofei; Shan, Wenya; Ma, Jingjiao; Cheng, Yuqiang; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Microbiology, 2017)
Shiga toxin-converting bacteriophages (Stx phages) carry the stx gene and convert nonpathogenic bacterial strains into Shiga toxin-producing bacteria. There is limited understanding of the effect that an Escherichia coli (E. coli) clustered regularly interspaced short palindromic repeats (CRISPR)-Cas adaptive immune system has on Stx phage lysogen. We investigated heat-stable nucleoid-structuring (H-NS) mutation-mediated CRISPR-Cas activation and its effect on E. coli Stx2 phage lysogen. The Δhns mutant (MG1655Δhns) of the E. coli K-12 strain MG1655 was obtained. The Δhns mutant lysogen that was generated after Stx phage lysogenic infection had a repressed growth status and showed subdued group behavior, including biofilm formation and swarming motility, in comparison to the wild-type strain. The de-repression effect of the H-NS mutation on CRISPR-Cas activity was then verified. The results showed that cas gene expression was upregulated and the transformation efficiency of the wild-type CRISPR plasmids was decreased, which may indicate activation of the CRISPR-Cas system. Furthermore, the function of CRISPR-Cas on Stx2 phage lysogen was investigated by activating the CRISPR-Cas system, which contains an insertion of the protospacer regions of the Stx2 phage Min27. The phage release and toxin production of four lysogens harboring the engineered CRISPRs were investigated. Notably, in the supernatant of the Δhns mutant lysogen harboring the Min27 spacer, both the progeny phage release and the toxin production were inhibited after mitomycin C induction. These observations demonstrate that the H-NS mutation-activated CRISPR-Cas system plays a role in modifying the effects of the Stx2 phage lysogen. Our findings indicated that H-NS mutation-mediated CRISPR-Cas activation in E. coli protects bacteria against Stx2 phage lysogeny by inhibiting the phage release and toxin production of the lysogen.